Student's Motivation Towards Extracurricular Scouts SD at Negeri 20 Sitiung Dharmasraya District: Motivasi Siswa Terhadap Ekstrakurikuler Pramuka Di SD Negeri 20 Sitiung Kabupaten Dharmasraya - rena dewita (Journal of Vocational Education and Information Technology (JVEIT), 2020)
This research aims to find out the interest of students in participating in extracurricular activities of scouts at SD Negeri 20 Sitiung. This method of research is quantitative descriptive research. The method used is the survey method. The population in this study is students of the 2019/2020 school year. This research sample is all students who must participate in scout extracurricular at SD N 20 Sitiung which numbered 21 students. The sampling technique used is proportional random sampling. The instrument used is a questionnaire. The analysis technique is to pour the frequency of the answer results using the likert scale. The results of this study showed that the interest of grade x students in participating in extracurricular scout activities at SD N 20 Sitiung is high with an average consideration of 92.36. Interest in grade x students in participating in extracurricular scout activities at SD N 20 Sitiung which is category; (a) very high 16 people or 24.62%; (b) a height of 38 persons or 58.46% ; (c) being 9 persons or 13.85% ; (d) low 2 persons or 3.08% ; (e) very low 0 person or 0%.